The use of physical characteristics to explain variation in ball-carrying capability in elite rugby union: a narrative review - Hart, A. S.; Erskine, R. M.; Clark, D. R. (The Journal of Strength and Conditioning Research, 2023)
The effectiveness of offensive ball carrying has been identified as a key determinant in elite rugby union try-scoring success and subsequent match outcome. Despite this, there is limited research evaluating the physical qualities believed to underpin the ball-carrying capability among elite rugby union players. The aim of this review was to critically appraise the scientific literature that has investigated the use of physical characteristics to explain ball-carrying capability in elite rugby union. Measures of sprint performance, specifically acceleration, maximum sprinting speed, and sprint momentum have presented weak-to-strong correlations with the number of tries scored, line breaks, tackle breaks, defenders beaten, and dominant collisions recorded among international rugby union players. In addition, unilateral and bilateral vertical countermovement jump height, peak power output, and drop jump reactive strength index have each demonstrated meaningful associations with the number of tries scored, line breaks, tackle breaks, and dominant collisions. However, various measures of maximal lower-body strength have presented only trivial correlations with the game statistics associated with ball-carrying capability. These trivial correlations are likely a result of the inconsistent and inaccurate methods used to assess maximal lower-body strength, with methods ranging from a box squat-predicted 1 repetition maximum to a maximal isometric mid-thigh pull. Further investigation is required to assess the contribution of maximal lower-body strength, agility, repeated sprint ability, and aerobic capacity to ball-carrying capability in elite rugby union. Such robust, objective data could be used to inform the specificity of physical preparation and maximize the transfer of these physical qualities to on-field performance.